(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Since a few years, smart devices have become an integral part of our daily lives. As a result, on smart devices, offering facilities and security is becoming more important. The goal of this article is to create a home automation system that works with Android mobile devices. Wi-Fi allows the mobile device and the system to communicate with one another. Current studies discusses the IoT-Based Smart Home Automation. Any suitable device may load the mobile application and interact with the system. Commands to turn on/off electrical equipment such as lights, fans, and air conditioners, as well as setting timers, can be delivered simply and fast from mobile devices through a simple and pleasant GUI application that is straightforward to use for any average user. The system then acts and responds to these orders by performing the tasks specified in the commands and informing the user of the outcome. Within Wi-Fi range, the user may also view the result on an Android mobile application. As a result, developing a home automation system for a luxury living that strives to create an advanced home automation system utilizing Wi-Fi technology is a solid option.